Structured Light Control and Diagnostics Using Optical Crystals - Angelsky, O. V.; Bekshaev, A. Y.; Dragan, G. S.; Maksimyak, P. P.; Zenkova, C. Yu.; Zheng, Jun (Frontiers in Physics, 2021)
We describe experimental results exposing the possibilities of optical crystals, especially anisotropic and birefringent, for creation, control, and diagnostics of structured light fields with singular and extraordinary properties. The efficiency of birefringent media is demonstrated for purposeful generation of optical beams with phase singularities (optical vortices) and desirable patterns of internal energy flows, in both the mono- and polychromatic light. On the other hand, anisotropic micro-objects can be used as probing bodies for investigation of the peculiar features of internal energy flows and corresponding momentum and angular momentum distributions in structured light fields. In particular, the specific mechanical action of light fields, formed under the total-reflection conditions, has been detected that confirms the existence of “extraordinary” dynamical characteristics of evanescent light waves predicted theoretically: the “transverse” momentum and “vertical” spin and their dependence on the incident beam polarization. The results can be useful for the optical trapping and micromanipulation techniques, including the biomedical and pharmaceutical applications.